Applying Marine Protected Area Frameworks to Areas beyond National Jurisdiction - Emily S. Nocito; Jenna Sullivan-Stack; Elizabeth P. Pike; Kristina M. Gjerde; Cassandra M. Brooks (Sustainability, 2022)
Marine protected areas (MPAs) can provide a range of ecological benefits. Frameworks—including the IUCN protected area categories and The MPA Guide—offer tools towards evaluating an MPA’s objectives, types, Level of Protection, and potential effectiveness. However, the majority of MPAs exist in national waters, raising the question of how these frameworks apply in areas beyond national jurisdiction (ABNJ). We evaluated the existing ABNJ MPAs in the Antarctic designated through the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) using the two above mentioned frameworks. The newly released The MPA Guide, which complements guidance from the IUCN protected area categories, provides perhaps the most exhaustive framework as it seeks to evaluate implementation, enabling conditions, and outcomes. The CCAMLR MPAs ranged from Category 1A (for IUCN)/Highly Protected (for The MPA Guide) to Category IV (for IUCN)/Lightly Protected (for The MPA Guide) due to differences in management objectives and activities occurring within the zones of the MPAs. Given ongoing negotiations for a new international, legally binding treaty for high seas biodiversity, evaluating an MPA using these existing frameworks will prove useful to allow for a full comprehensive picture of an MPA and what it can expect to achieve.